Penerapan Wayground dalam Meningkatkan Kepuasan Mahasiswa Pada Mata Kuliah Pendidikan Pancasila - Hamdani, Hamdani; Rizki Asrul, Muhammad; Haidah , Haidah; Rahman, Abdul; Jamilah, Meilan; Kusnandar, Amat (Universitas Muhammadiyah Ponorogo, 2026)
The digital transformation in higher education demands innovation in learning evaluation systems to make them more interactive, transparent, and adaptive to the characteristics of the digital generation. This study aims to analyze the level of student satisfaction with the use of Wayground (formerly Quizizz) as a digital evaluation medium in the Pancasila Education course, which focuses on value-based and character-oriented learning. This research employed a quantitative descriptive approach using a survey method, with a questionnaire administered to 136 first-semester students of the Business Administration Study Program at Politeknik Negeri Samarinda, selected through cluster sampling. Data were analyzed descriptively by calculating the mean scores and satisfaction index using a Likert scale of 1–5. The findings indicate that student satisfaction falls within the “satisfied” category, with an overall mean score of 3.87. The highest-rated indicator was visual appeal and interface design (mean 4.09), while the lowest was learning motivation (mean 3.66). These results suggest that Wayground is effective in enhancing the efficiency, objectivity, fairness, and accessibility of learning evaluations while reinforcing technology acceptance (Technology Acceptance Model) within value-based education contexts. The novelty of this research lies in the implementation of a digital gamification platform within an ideological course, an area that has been rarely explored in previous studies.